2019
DOI: 10.1093/jxb/erz269
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of seed dormancy by the maternal environment is instrumental for maximizing plant fitness in Polygonum aviculare

Abstract: The maternal environment during the reproductive phase in Polygonum aviculare regulates the dormancy level of seeds so that those dispersed at different times all germinate within an optimal period. Photoperiod plays an important role in this regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…reproduction and seed dispersal), and not only relative to environment, but also to agricultural practices and crop phenology, defining the fitness of a weed population in a certain environment. 25 From this we can argue that weed behavior in a changing agricultural scenario can be inferred from an analysis of the dormancy attributes, at least better than from other demographic features. More precisely, dormancy attributes and their plasticity cannot predict success by themselves, but they can predict failure and the recruitment of new species in the weed community.…”
Section: Can We Consider Dormancy Attributes To Derive Lines Of Actiomentioning
confidence: 97%
See 3 more Smart Citations
“…reproduction and seed dispersal), and not only relative to environment, but also to agricultural practices and crop phenology, defining the fitness of a weed population in a certain environment. 25 From this we can argue that weed behavior in a changing agricultural scenario can be inferred from an analysis of the dormancy attributes, at least better than from other demographic features. More precisely, dormancy attributes and their plasticity cannot predict success by themselves, but they can predict failure and the recruitment of new species in the weed community.…”
Section: Can We Consider Dormancy Attributes To Derive Lines Of Actiomentioning
confidence: 97%
“…This plasticity allows P. aviculare to behave as a weed of either winter or summer crops. Recent results showed that the requirement of low temperatures for dormancy alleviation in P. aviculare also depends on the maternal environment perceived by the seeds during their development and maturation on the mother plant, further increasing the plasticity in the requirement of low temperatures for decreasing the dormancy level in the seed‐bank population …”
Section: Seed Dormancy As a Trait For Adjustment: Stories Of Evolutiomentioning
confidence: 99%
See 2 more Smart Citations
“…2011; Fernández Farnocchia et al . 2019); and (ii) maternal genetic effects, where phenotypic differences in the offspring are due to the maternal parent´s phenotype or genotype (Roach & Wulff 1987; Pace et al . 2015; Singh et al .…”
Section: Introductionmentioning
confidence: 99%